Trade fair fee as a source of income for the budgets of municipalities in Poland on selected examples - Cezary Szydłowski (Financial Internet Quarterly, 2020)
The public finance system in force in Poland provides for a trade fair fee (Polish - "op±ata targowa") as part of municipalities' own revenues. The trade fair fee is collected from persons selling at marketplaces located in the municipality. It constitutes own income for the commune's budget and is an archaic form of public tribute. According to the legal regulations in force in Poland, communes may waive the collection of the exhibition fee, however, there are still many communes collecting it. The assessment of income to the commune budget from the trade fair fee was carried out on the basis of a survey of income to the budget of selected 10 coastal communes in Pomorskie Voivodeship. The selection of coastal municipalities was determined by their specificity in terms of retail trade on markets and squares. This is because the holiday season attracts many tourists and entrepreneurs who sell the goods they offer in the mode of direct retail trade carried out on local markets, streets or squares (often located near the entrance to local beaches). The analysis of income from the fair fee was carried out on the basis of reports on the implementation of the budgets of communes and reports on the income of communes Rb-27s published by commune authorities on the pages of the Public Information Bulletin of a given local government unit.
Keywords: H71; H83; 330; audit; budget revenues; local tax; public finance; local government; trade fair fee